Prevalence of Deliberate Self-harm Among Chinese Patients With Heroin Dependence: A Meta-Analysis - Zhong, Bao-Liang; Xu, Yan-Min; Xie, Wu-Xiang; Chen, Wen-Cai; Lu, Jin (Frontiers in Psychiatry, 2018)
Background: There is paucity of data regarding the prevalence and methods of deliberate self-harm (DSH) in patients with heroin dependence in international literature. In China, there have been a few studies investigating the prevalence of DSH in heroin-dependent patients (HDPs), but their rates varied widely. We thus conducted a meta-analysis of studies assessing the prevalence of DSH among Chinese HDPs. Methods: Relevant studies were retrieved from major Chinese databases (China National Knowledge Infrastructure, Wanfang data, and SinoMed) and western databases (PubMed, EMBASE, and PsycInfo). Two authors independently identified eligible studies and extracted data. Studies that included a representative sample of Chinese HDPs and ascertained DSH caseness in a reliable way were considered as high quality. Statistical analysis was performed using R software. Results: In total, 15 eligible studies with a total of 37243 Chinese HDPs were included. All included studies were conducted in heroin detoxification settings. Only two studies were rated as high quality. The pooled prevalence of DSH in Chinese HDPs was 4.4% (95%CI: 2.9%, 6.2%), but the heterogeneity of prevalence rates across studies was significant (I2=98%, P<0.001). Studies rated as high quality had significantly higher prevalence of DSH than those rated as low quality (13.2% vs. 3.4%, P<0.001). Swallowing foreign objects was the most common method of DSH, with a combined prevalence of 2.7% (95%CI: 1.6%, 4.4%). Extreme DSH methods such as cutting off fingers and jumping from height were also not uncommon in this patient population. Conclusion: Due to methodological problems in available studies, we find a relatively low prevalence of DSH among Chinese HDPs receiving detoxification treatment. Nevertheless, the self-harmers of Chinese HDPs are more likely to harm themselves in a dangerous or life-threatening way. Restricting the availability of DSH methods may be an effective way to prevent or reduce DSH in China’s detoxification treatment settings.